Sperm gamma-Aminobutyric acid type A receptor delta subunit (GABRD) and its interaction with purinergic P2X2receptors in progesterone-induced acrosome reaction and male fertility - Xu, W.; Wang, K.; Chen, Yan; Liang, X.; Yu, M.; Yue, H.; Tierney, M. (C S I R O Publishing, 2017)
© CSIRO 2017. The mechanism underlying the non-genomic action of progesterone in sperm functions and related Ca2+ mobilisation remains elusive. Herein we report the expression of gamma-Aminobutyric acid type A receptor delta subunit (GABRD) in human and rodent sperm and its involvement in mediating the progesterone-induced acrosome reaction. GABRD was localised in the sperm head/neck region. A d(392-422)-specific inhibitory peptide against GABRD blocked the progesterone-induced acrosome reaction and the associated increase in intracellular Ca2+. Similarly, an inhibitory effect against both progesterone-induced Ca2+ influx and the acrosome reaction was observed with a P2X2 receptor antagonist. The lack of synergism between the GABRD and P2X2 inhibitors suggests that these two receptors are playing a role in the same pathway. Furthermore, a co-immunoprecipitation experiment demonstrated that GABRD could undergo protein-protein interactions with the Ca2+-conducting P2X2 receptor. This interaction between the receptors could be reduced following progesterone (10M) inducement. Significantly reduced GABRD expression was observed in spermatozoa from infertile patients with reduced acrosome reaction capacity, suggesting that normal expression of GABRD is critical for the sperm acrosome reaction and thus male fertility. The results of the present study indicate that GABRD represents a novel progesterone receptor or modulator in spermatozoa that is responsible for the progesterone-induced Ca2+ influx required for the acrosome reaction through its interaction with the P2X2 receptor.